Manejo das doenças renais na atenção primária a saúde: revisando papéis e propondo roteiros para as práticas - Alves, Pablo Rodrigues Costa (2020)
The chronic kidney disease patient (CKD) has several clinical, social, and psychological challenges, in addition to the kidney disease itself. When commencing treatment with a nephrologist, the patient usually focuses her/his concerns on the specialist in nephrology, limiting her/his care plan to renal dysfunction and its complications, renal replacement therapy (when on dialysis), and related clinical problems such as cardiovascular disease. This practice deviates from the Ministry of Health's proposal to centralize the health needs of individuals in Primary Health Care, whereby the primary care physician (PCP) would be the care coordinator. Contrary to the recommendation of the ministry, several authors suggest that the nephrologist has assumed the role of primary care provider/coordinator, while the PCP has a secondary role or none at all in assisting this group of patients. Several authors point out that the low participation of the PCP in the care of these patients is due to multiple factors, above all due to the fact that nephrologists, PCPs, and patients have doubts about the PCP's skills in managing primary health problems and in coordinating the care of this complex group of patients. The scarcity of resources related to nephrology and CKD, oriented towards the PCP and Primary Health Care (PHC), in the portals of the Ministry of Health and the Department of Primary Health Care, can contribute to the insecurity of the PCP when approaching patients with CKD. In this vein, this paper presents the book titled "How to manage kidney diseases in primary health care" with the proposal of contributing to the continued education of doctors working in PHC. In addition, other products are also introduced: longitudinal follow-up cards of patients with CKD, educational materials for patients with CKD, and an integrative review titled “Coordination of primary care for patients with chronic kidney disease on dialysis: reevaluating roles ”.